Studi Tingkat Kekritisan Lahan Sebagai Dasar Arahan Rehabilitasi Hutan Dan Lahan Das Marisa Di Kabupaten Pohuwato Provinsi Gorontalo - Wolok, Estefanus; Suhartanto, Ery; Harisuseno, Donny (Fakultas Teknik, Universitas Brawijaya, 2014)
The forest degradation rate reached 2,83 million ha every year. From the total forest area of 120,5 million ha, about 59 million ha were critical areas. Besides, the critical Watersheds ini Indonesia increased. The watershed conservation efforts had brought motivation to develop the erosion estimation technologies that could assist in solving the erosion rate estimation problems spatially. The study was carried out at Marisa Watershed, Pohuwato Regency of Gorontalo Province. The results showed that the value of erosion rate in Marisa Watershed area was 169,364 ton/ha/year or 14,114 mm/year where the Marisa Watershed total wide was 14.842,5 ha. Whereas the sediment potential was 125,299 ton/year and runoff was 197,779 mm/year. The Erosion Danger Level was 3.654,146 ha (14,71%) hard and 3.353,834 ha (13,50 %) very hard. One of the assumptions why the land erosion rate was very high was because of the misuse of the land and geology condition at Marisa Watershed.To control the erosion rate, focussed to the recommendation of land utilization direction that referred to The Forest - Soil Conservation and Rehabilitation Program (ARHL) and building of 6 check dam. Meanwhile, the land utilization should notice The RTRW and the cooperation between local inhabitant and the government was needed indeed in the soil conservation and land rehabilitation efforts.Key Words: Erosion, Sediment, Run Off, Soil Conservation.